Negative Parity States in 39Cl Configured by Crossing Major Shell Orbits*Supported by JSPS and CNRS under the Japan-France Research Cooperative Program, the Grant-in-Aid for Scientific Research on Innovative Areas "Toward new frontiers: Encounter and synergy of state-of-the-art astronomical detectors and exotic quantum beams", JSPS/MEXT KAKENHI under Grant Nos JP18HO3692 and JP18H05462, the National Key R&D Program of China (2018YFA0404403), and the National Natural Science Foundation of China Nos 11775316, 11535004, 11875074 and 11875073. (May 2019) - Tao 陶, Long-Chun 龙春; Ichikawa, Y.; Yuan 袁, Cen-Xi 岑溪; Ishibashi, Y.; Takamine, A.; Gladkov, A.; Fujita, T.; Asahi, K.; Egami, T.; Funayama, C.; Imamura, K.; Lou 楼, Jian-Ling 建玲; et al.
Abstract : Traditional "magic numbers" were once regarded as immutable throughout the nuclear chart. However, unexpected changes were found for unstable nuclei around N = 20. With both proton and neutron numbers around the magic number of 20, the neutron-rich 39 Cl isotope provides a good test case for the study of the quantum-state evolution across the major shell. In the present work, the negative parity states in 39 Cl are investigated through the β decay spectroscopy of 39 S. Newly observed γ transitions together with a new state are assigned into the level scheme of 39 Cl. The spin parity of 5/2 − for the lowest negative parity state in 39 Cl is reconfirmed using the combined γ transition information. These systematic observations of the negative parity states in 39 Cl allow a comprehensive comparison with the theoretical descriptions. The lowest 5/2 − state in 39 Cl remains exotic in terms of comparisons with existing theoretical calculations and with the neighboring isotopes having similar single-particle configurations. Further experimental and theoretical investigations are suggested.